It only works if we all participate. A response to ‘Diamond is a scientist’s best friend. Counteracting systemic inequality in open access publishing.’ - van Charldorp, Tessa; Labrie, Nanon (Dutch Journal of Applied Linguistics, 2024)
As the chair of Anéla (Dutch Society for Applied Linguistics) and chair of VIOT (Vereniging Interuniversitair Overleg Taalbeheersing) we respond to the position paper by Andringa, Mos, van Beuningen, Gonzalez, Hornikx and Steinkraus (2024) titled ‘Diamond is a scientist’s best friend. Counteracting systemic inequality in open-access publishing.’ We suggest some additional actions we can undertake as associations within the fields of applied linguistics and language and communication to achieve the goal set out by the authors: making Diamond Open Access publishing the standard in publishing. We conclude by adding two more benefits when doing so.